Fourth CAADP Biennial Review Brief: Angola. Africa Agriculture Transformation Scorecard Performance and Lessons - Kasoma-Pele, W.; Matchaya, Greenwell C.; Manuvanga, K. (Regional Strategic Analysis and Knowledge Support System (ReSAKSS), 2025)
The Malabo Declaration on accelerated agricultural growth and transformation for shared prosperity and improved livelihoods is a set of goals adopted by Heads of State and Government of the African Union in 2014 in Malabo, Equatorial Guinea (AUC 2014). To translate the seven Malabo commitments into results, a call for action was made by the Heads of State and Government for the African Union Commission (AUC) and the African Union Development Agency NEPAD (AUDA-NEPAD), in collaboration with partners, to initiate a review process to be conducted on a biennial basis starting 2017, with an objective of tracking, measuring, and reporting progress toward achieving the Malabo Declaration commitments by 2025.